A Novel Sandwich-type Dinuclear Complex for High-capacity Hydrogen Storage - 朱海燕 陈元振 李赛 曹秀贞 柳永宁 (Chinese journal of chemistry, 2012)
From density functional theory （DFT） calculations, we predicted that the sandwich-type dinuclear organometallic compounds Cpffi2 and Cp2Sc2 can adsorb up to eight hydrogen molecules respectively, corresponding to a high gravimetric storage capacity of 6.7% and 6.8% （w）, respectively. These sandwich-type organometallocenes proposed in this work are favorable for reversible adsorption and desorption of hydrogen at ambient conditions.